Effects of Teaching Health Care Workers on Diagnosis and Treatment of Pesticide Poisonings in Uganda. (28th August 2017) - Sibani, Claudia; Jessen, Kristian Kjaer; Tekin, Bircan; Nabankema, Victoria; Jørs, Erik
Background: Acute pesticide poisoning in developing countries is a considerable problem, requiring diagnosis and treatment. This study describes how training of health care workers in Uganda affects their ability to diagnose and manage acute pesticide poisoning. Method: A postintervention cross-sectional study was conducted using a standardized questionnaire. A total of 326 health care workers in Uganda were interviewed on knowledge and handling of acute pesticide poisoning. Of those, 173 health care workers had received training, whereas 153 untrained health care workers from neighboring regions served as controls. Results: Trained health care workers scored higher on knowledge of pesticide toxicity and handling of acute pesticide poisoning. Stratification by sex, profession, experience, and health center level did not have any influence on the outcome. Conclusions: Training health care workers can improve their knowledge and treatment of pesticide poisonings. Knowledge of the subject is still insufficient among health care workers and further training is needed.